Legal Protection For The Community Of Medan City Against The Installation Of Electricity Poles (Case Study At The State Electricity Company) - Rindu Lenggit Dalimunthe; Ramadani Ramadani (LEGAL BRIEF, 2026)
This study examines the legal protection perceived by the people of Medan City regarding the installation of electricity poles, with a focus on the company responsible for installing them, namely the State Electricity Company (PLN). The background of this research is based on the limited public knowledge of legal provisions governing both corporate and state authority, as well as the inconsistency between electricity infrastructure development and citizens’ land rights and safety guarantees. These conditions often lead to problems such as land disputes or disturbances caused by electricity poles located on privately owned property. The purpose of this study is to analyze the forms of legal protection regulated under Law Number 30 of 2009 on Electricity and to identify the obstacles and solutions in its implementation in Medan City. This research uses an empirical juridical approach with a case study method, involving the analysis of legal documents, interviews with residents to examine the reality of legal protection, interviews with company representatives to understand the actual mechanisms for pole installation and the protection measures applied, and direct field observations at pole installation sites. The results of the study indicate that the reality of legal protection for residents remains relatively weak, particularly in the processes of permit management and the fulfillment of compensation. This is reflected in cases involving PLN that have generated public complaints regarding a lack of transparency and limited public participation. The study concludes that there is a need to educate the community to participate more actively and to improve their understanding of legal protection as consumers, as well as to recognize the gap between regulatory frameworks and their practical implementation in providing legal protection